Practice Patterns of Infusion-related Reaction Prophylaxis in Breast Cancer Patients Receiving Chemotherapy at K Hospital - Thi Thu Trang, Tran; Minh Thu, Hoang Thi; Dinh Tien, Vu; Tu Son, Nguyen; Thi Lien Huong, Nguyen; Thi Quynh Anh, Tran; Thi Hong Hanh, Nguyen (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 42 No 1SDO - 10.25073/2588-1132/vnumps.4984, 2026)
Objective: To analyze the status of premedication and its association with the incidence of infusion-related reactions (IRRs) in breast cancer patients receiving chemotherapy. Subject and method: A prospective descriptive study was conducted among 219 patients aged ≥18 years diagnosed with breast cancer and receiving inpatient chemotherapy at the Departments of Internal Medicine 5 and 6, K Hospital, from January 1, 2024, to March 31, 2024. Result: The mean age was 50.4 ± 10.2 years; 48.4% of patients received taxane-containing regimens requiring IRR prophylaxis. IRR prophylaxis was administered in 72.6% of patients, including all taxane-containing regimens. A combination of dexamethasone, diphenhydramine, and famotidine (63.6%) was the most common premedication regimen, similarly observed in both taxane-containing (68.6%) and non-taxane regimens (53.7%). Assessment of guideline adherence showed that 50.3% of prophylaxis was appropriate, while 49.7% was inappropriate, including 44.7% overprophylaxis and 5.0% inadequate prophylaxis. 16.4% of patients witnessed IRRs, of whom 5.5% required discontinuation of infusion. A history of previous IRR was linked to an increased risk of both any-grade IRR and infusion discontinuation (p<0.05). Prior pruritus and inadequate prophylaxis was significantly associated with a noticeably higher risk of IRR (p<0.05) but not infusion discontinuation (p>0.05). Notably, over-prophylaxis showed no association with IRR risk of any severity or infusion discontinuation (p>0.05). Conclusion: Approximately half of the patients received inappropriate IRR prophylaxis, mainly due to over-prophylaxis. Prior IRR, prior-cycle pruritus, and inadequate prophylaxis are associated with IRR outcomes, highlighting the importance of guideline adherence and individualized prophylaxis strategies.